Storytelling - Kaebnick, Gregory E. (The Hastings Center report, 2019)
The November–December issue of the Hastings Center Report features a set of essays on the ethics of writing stories of patient care. The Report regularly features such stories, but some ways of telling them would be plainly unacceptable, and some in bioethics have suggested that the bar for acceptability is very high. Tod Chambers takes that position in this essay set. Drawing on the work of the literary theorist Mikhail Bakhtin, he proposes that case studies should be “polyphonic”—meaning that they contain “a diversity of voices that are unmediated and distinct.” In effect, he calls for a kind of coauthoring of stories about patients. In a second essay, Arthur Frank also calls for including the patient’s voice, but he builds on Bakhtin’s call for “dialogic” storytelling, in which the author seeks to represent the characters in the story as having their own voices and their own lives: “they can talk back.” A third essay, by Philip Rosoff, is concerned about the problem of harm and patient anonymity, which in the contemporary media environment has become harder to address.